2011
DOI: 10.5935/1678-9741.20110005
|View full text |Cite
|
Sign up to set email alerts
|

Insuficiência renal oculta acarreta risco elevado de mortalidade após cirurgia de revascularização miocárdica

Abstract: Insuficiência renal oculta acarreta risco elevado de mortalidade após cirurgia de revascularização miocárdicaHidden renal dysfunction causes increased inhospital mortality risk after coronary artery bypass graft surgery

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Despite recent advances in cardiovascular surgery kidney dysfunction is highly prevalent [1][2][3][4][5][6][7][8]. When dialysis is performed the mortality rate is increased by up eight times [9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent advances in cardiovascular surgery kidney dysfunction is highly prevalent [1][2][3][4][5][6][7][8]. When dialysis is performed the mortality rate is increased by up eight times [9].…”
Section: Introductionmentioning
confidence: 99%
“… 4 Volkmann et al found that a preoperative SCr level >1.5 mg/dL doubled the risk of death and also produced a longer hospital stay. 15 Our previous study also showed that a preoperative SCr level >106 μmol/L is an important independent risk factor for postoperative AKI. 16…”
Section: Discussionmentioning
confidence: 85%
“…However, most studies about preoperative renal dysfunction usually studied patients with eGFR < 60 mL/min /1.73 m 2 [6, 14], but the risk of patients with mild decreased eGFR (60~90 mL/min /1.73 m 2 ) and normal SCr is less evaluated. In the study by Howell et al including 7621 consecutive patients who underwent CABG, valve surgery or combined procedures, eGFR ≥ 90 mL/min /1.73 m 2 were considered normal renal function (reference group), eGFR 60–90 mL/min/1.73 m 2 were mild renal dysfunction (group 2), eGFR 30–59 mL/min/ 1.73 m 2 were moderate renal dysfunction (group 3) and eGFR 15–29 mL/min/1.73 m 2 were severe renal dysfunction (group 4) and the results showed that eGFR of 60–90 mL/min/1.73 m 2 (mild renal dysfunction) was an independent predictor of in-hospital and late mortality as well as cardiovascular complications [15], which is in line with our results, which revealed that for patients with normal SCr under the age of 65 years preoperative 60 ≤ eGFR< 90 mL/min/1.73 m 2 values became a risk factor for 3-year progressive CKD.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Volkmann et al, patients with plasma creatinine (PCr) ≤ 1.5 mg/dL who underwent CABG were divided into 2 groups, estimated creatinine clearance (eCrCl) ≥ 60 mL/min (normal renal function) or eCrCl < 60 mL/min (reduced renal function), respectively. The results showed that reduced renal function had a double risk of death, a longer total hospital stay and post-surgical hospital stay than those patients with normal renal function [6]. However, a considerable fraction of cardiac surgery patients may have normal SCr values and an eGFR under 90 mL/min/1.73 m 2 , but above 60 mL/min/1.73 m 2 , particularly since eGFR declines with age [7].…”
Section: Introductionmentioning
confidence: 99%